Lagrangian coherent structures and physical processes of coastal upwelling - (:unkn) unknown (My University, 2019)
Studying physical processes of an upwelling system is essential to understand its present variability and its past and future changes. This thesis presents an interdisciplinary study of the coastal upwelling system from different satellite acquired data, with the main focus placed on the North West African (NWA) upwelling system. This interdisciplinary study covers (1) the problem of the automatic identification and extraction of the upwelling phenomenon from biological and physical satellite observations. (2) A statistical study of the spatio-temporal variation of the NWA upwelling throughout its extension and different upwelling indices. (3) A Study of the nonlinear relationships between the surface mixing and biological activity in the upwelling regions. (4) Lagrangian studies of coherent eddies; their physical properties and automatic identification. (5) The study of transport made by Lagrangian eddies off the NWA Upwelling and their impact on the open ocean. [...]
Keywords: African Research